RISK FACTORS, MICROBIOLOGICAL SPECTRUM, ANTIBIOTIC SENSITIVITY AND OUTCOMES OF VENITILATOR ASSOCIATED PNEUMONIA IN NEONATES: A STUDY FROM A TERTIARY CARE HOSPITAL IN SOUTHERN ASSAM - CHIKKAMATH, VEERANNA SHIVANAND; PATIL, M. SWATHI; BISWAS, NILANJAN; DAS, PRANAB; CHOUDHURY, SUJIT NATH (International Journal of Current Pharmaceutical Research, 2026)
Objective: To determine the incidence, microbiological profile, antibiotic sensitivity, risk factors, and outcomes of VAP in neonates. Methods: This prospective observational study, conducted for one year in a tertiary care NICU in Southern Assam, included 101 neonates ventilated for over 48 h. VAP was defined using CDC criteria, integrating clinical, Laboratory, radiological, and microbiological findings. Data on patient characteristics, VAP occurrence, microbiology, and antibiotic susceptibility were collected and analysed. Results: Thirty-seven (36.7%) neonates developed VAP, resulting in an incidence of 41.11 per 1,000 ventilator days. Key risk factors significantly associated with VAP included prematurity, low birth weight, bronchopulmonary dysplasia, and asphyxia. Common clinical signs were new onset tachypnoea and increased respiratory secretions. VAP led to significantly longer hospital stays (38.1±17.82 vs. 21.4±14.3 d, p=0.0001) and mechanical ventilation durations (13.42±8.74 vs. 5.89±3.56 d, p=0.0001), alongside increased antibiotic use. Gram-negative organisms predominated (68.9% of 45 isolates), notably multi-drug resistant (MDR) Acinetobacter spp. and ESBL-producing Klebsiella pneumoniae/oxytoca. Pseudomonas isolates showed high resistance to Amikacin, Meropenem, and Piperacillin+Tazobactam. MRSA exhibited good Linezolid susceptibility. VAP is associated with increased morbidity and mortality. Conclusion: Neonatal VAP imposes a substantial burden, driven by prematurity, severe underlying conditions, and a high prevalence of MDR Gram-negative pathogens. Our findings highlight the urgent need for robust infection control, vigilant surveillance, and culture-guided antibiotic therapy to optimize outcomes and combat antimicrobial resistance. Larger, multi-center studies are essential.